Geolinguistics in the linguocognitive learning model: The experience of teaching hydronyms in universities in Kazakhstan - Dautkulova, Akmaral; Atabayeva, Mereke; Gulmira, Madiyeva; Rakhmetov, Maxot (International Journal of Innovative Research and Scientific Studies, 2025)
The article examines the role of hydronyms as linguistic and cognitive units in the system of teaching geolinguistics at universities in Kazakhstan. The study was conducted within the framework of descriptive and cognitive approaches, based on the ethnographic analysis methodology (according to Spradley, 2013) and methods of interpreting linguistic data (according to Sudaranto, 2015). The empirical base includes written sources (toponymic dictionaries, maps, regional reference books) and oral materials collected during semi-structured interviews with native speakers and students of linguistics. The analysis covers three areas: (1) etymology and semantics of hydronyms, including the origin of the names and their relation to the natural and climatic conditions of the region; (2) morphological structure and cognitive schemes reflecting the features of conceptualization of water bodies in linguistic consciousness; (3) philosophical and cultural understanding of hydronyms, where the names of water bodies are interpreted as a reflection of human interaction with nature, the spiritual world, and the social environment. The results of the study show that hydronyms carry culturally significant concepts, such as: human and nature (water as a symbol of life, path, purification); human and the sacred (the connection of water with religious and mythological concepts); linguistic diversity, where elements of Kazakh, Russian, Turkic, and Arabic languages are combined in the structure of hydronyms. Teaching geolinguistics based on a linguocognitive approach and the analysis of hydronyms contributes to the development of spatial thinking, ethnocultural competence, and an interdisciplinary view among students of philological and pedagogical fields. This is especially relevant in the context of multilingualism and cultural diversity in Kazakhstan.